Coastal Area Waste Sources, Indonesia: A Review - Pebriyanto Setiawan; Wa Janaria Rumbia (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Waste is a waste product from various human activities that can pollute the environment, especially in coastal areas. This literature review examines various sources of waste, including household waste, industrial waste, and tourism activities, and their impacts on public health and marine ecosystems in coastal areas. Objective: This literature review is to review scientific articles on coastal area waste sources in Indonesia. Methods: The Systematic Literature Review (SLR) was used with journal selection using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) flow. The journals used were journals published from 2016 to 2025. The journal search was carried out using the keyword, coastal area waste sources. Results: The selected articles came from Indonesia. Based on the literature review that has been conducted, it shows that people's behavior that is less aware of the importance of waste management contributes greatly to pollution. The level of public knowledge about the impact of waste is still low, which results in a lot of waste being disposed of carelessly. A significant relationship between waste disposal behavior and public health is indicated by the high prevalence of pollution-related diseases, such as diarrhea and skin diseases. Conclusion: To overcome this problem, intensive education efforts, provision of adequate waste management facilities, and stricter law enforcement are needed. Effective waste management is expected to improve the quality of public health and the sustainability of the coastal environment.